Penyesuaian Sosial Berdasarkan Adversity Quotient pada Mahasiswa Rantau - Yuliezar Perwira Dara; Sayidah Hilmi Dewi; Faizah Faizah; Ulifa Rahma (Universitas Negeri Surabaya, 2020)
The purpose of this study was to determine the role of the adversity quotient on social adjustment among students who are migrating from their home regions to the Malang City, East Java, for studying at universities. The sample was 164 students who are in the first year of their studies. Data were collected using Adversity Response Profile (ARP) and Student Adaptation to College Questionnaire (SACQ) and are analyzed using simple linear regression. The result showed that there is positive correlation between adversity quotient and social adjustment among the participants. It can be concluded from this study that the participants adversity quotient can affect their social adjustment. The increase of adversity quotient will predict better social adjustment.Keywords: Adversity quotient, migrating students, social adjustment.Abstrak: Penelitian ini bertujuan untuk mengetahui peran adversity quotient pada mahasiswa luar kota dalam membentuk penyesuaian sosial. Subjek penelitian adalah 164 mahasiswa perantauan yang menjalani studi mereka pada tahun pertama di Malang, Jawa Timur. Pengumpulan data dilakukan melalui skala Adversity Response Profile (ARP) dan Student Adaptation to College Questionnaire (SACQ). Data dianalisis menggunakan teknik analisis regresi linear sederhana. Hasil penelitian menunjukkan bahwa terdapat korelasi positif antara adversity quotient dengan penyesuaian sosial pada mahasiswa rantau yang sedang kuliah pada tahun pertamanya. Penelitian ini menyimpulkan bahwa adversity quotient pada partisipan dapat mempengaruhi kemampuan penyesuaian sosial mereka. Peningkatan adversity quotient dapat memprediksi penyesuaian sosial yang lebih baik.